Sympotthastia wuyiensis sp. n. from China, with description of the immature stages of S. takatensis (Tokunaga) (Diptera, Chironomidae) - Liu, Wenbin; Ferrington, Leonard C. Jr; Wang, Xinhua (Zootaxa, 2016)
Sympotthastia wuyiensis sp. n. is described and illustrated as male imago from China. The immature stages of S. takatensis (Tokunaga) are described. The generic diagnosis is emended. Key to the known adult males, larvae and pupae of the genus worldwide is presented.